1982
DOI: 10.1002/ana.410120604
|View full text |Cite
|
Sign up to set email alerts
|

Pathological findings underlying focal temporal lobe hypometabolism in partial epilepsy

Abstract: Histopathological studies were carried out on temporal lobe tissue from 25 patients with partial complex seizures who were studied by interictal positron computed tomography (PCT) with 18F-fluorodeoxyglucose and subsequently underwent anterior temporal lobe resection. Abnormalities were identified on x-ray computed tomographic scans in 7 patients, but none indicated the site of a pathologically confirmed structural lesion. Hypometabolic zones were observed on PCT scans of 22 patients and corresponded to focal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
118
0
6

Year Published

1984
1984
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(130 citation statements)
references
References 25 publications
6
118
0
6
Order By: Relevance
“…Histopathological studies have revealed hypometabolic areas at the focus of epileptic crises, 12,13 with synapse and neuronal activity losses in the presence of disorders arising from epilepsy. According to several authors, [14][15][16][17][18][19][20] dendritic and neuronal losses are always present in epileptic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological studies have revealed hypometabolic areas at the focus of epileptic crises, 12,13 with synapse and neuronal activity losses in the presence of disorders arising from epilepsy. According to several authors, [14][15][16][17][18][19][20] dendritic and neuronal losses are always present in epileptic patients.…”
Section: Discussionmentioning
confidence: 99%
“…We administered the drug twice a day, which suggests that new GABA-T synthesis does not exceed the number of enzyme molecules eliminated by GVG during the intervals between drug administration. The histopathological findings from the brains of drug-resistant epileptics show that in partial epilepsy gliosis increases, especially in the limbic structures (Engel et al, 1982). GABA-T is localized in neurons but also in glial cells (McGeer & McGeer, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Propagation to the ipsilateral PC, MC, and the AM required a mean of 5.6 (range, 3-8), 20.3 (range, [19][20][21][22], and 17.5 (range, 16-20) stimulations, respectively. Propagation to the AM became bilateral in three animals (AC3990, AC#992, AC#997), with a mean of 64 (range, 13-77) stimulations.…”
Section: Primary Site Kindlingmentioning
confidence: 99%